Factors That Affect Employee Productivity (Case Study at PT. Sagami Indonesia) - Purwanti Purwanti; Martua Sitorus (Institute of Computer Science (IOCS), 2018)
The productivity depression of PT. Sagami Indonesia was influenced by some situations in the organization which were discipline, and job satisfaction. Therefore researchers interested in examining the affect factors employee productivity. This research used descriptive quantitative method of statistic. Primary data were collected by questionnaire with Likert scale and 5 (five) choice of answers. The questionnaire was distributed to all employees other than manager. The results showed that: (1) the effect of discipline on employees’ productivity was positive and significant; (2) the effect of job satisfaction on employees’ produtivity was positive and significant;(3) the effect of discipline dan job satisfaction on employees’ productivity be simultaneously was positive and significant. Therefore, in terms of achieving the better employees’productivity, PT. Sagami Indonesia is expected to make some improvements on discipline and job satisfaction.